Suppressor of cytokine signaling 6 can enhance epidermal growth factor receptor signaling pathway in Bombyx mori (Dazao). (April 2018) - Abbas, Muhammad Nadeem; Kausar, Saima; Sun, Yu-Xuan; Tian, Ji Wu; Zhu, Bao-Jian; Liu, Chao-Liang
Abstract: The SOCS (Suppressor of cytokine signaling) family members are a potential negative regulator of cytokine signaling pathway and play a key role to maintain immunological functions in animals. SOCS-6 is an important member of the SOCS family, however the functions of this gene have rarely been explored among eukaryotes. Herein, we cloned and expressed SOCS-6 gene from Bombyx mori (Dazao) (BmSOCS-6), and anti-rabbit antibodies were prepared using purified recombinant BmSOCS-6 protein. Under normal physiological conditions, the BmSOCS-6 expression was observed at varied levels in six tissues, with most greatly expressed in fat body and hemocytes. After immune challenge with viral, fungal and bacterial pathogens, the BmSOCS-6 showed distinctly varied expression patterns in tissue, time and microbe dependent manner. By contrast, recombinant BmSOCS-6 protein strongly enhanced the expression of epidermal growth factor receptor (EGFR) pathway related genes, while the depletion of BmSOCS-6 by double stranded RNA suppressed their production. Altogether we concluded that BmSOCS-6 may improve the efficiency of EGFR signaling pathway in B. mori (Dazao). Highlights: A BmSOCS-6 gene was firstly identified from B. mori (Dazao). BmSOCS-6 ubiquitously expressed in different tissue as well as in developmental stages. BmSOCS-6 transcript in fat body and hemocytes was up-regulated following pathogen challenge. BmSOCS-6 was involved in the regulation of epidermal growth factor receptor pathway.